1999
DOI: 10.1053/jvet.1999.0256
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Propofol Usage With Postoperative Wound Infection Rate in Clean Wounds: A Retrospective Study

Abstract: Propofol is a lipid-based emulsion capable of supporting microbial growth. Administration of a potentially contaminated solution may contribute to surgical wound infection or other patient morbidity or mortality. Strict aseptic technique in the preparation of the solution and prompt disposal of unused drug are imperative to curtail the potential for extrinsic contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 17 publications
0
53
1
2
Order By: Relevance
“…Previous epidemiologic studies of wound infection rate also found that older animals (>8years) were more likely to develop SSI. 23 Duration of anesthesia, previously found to be a significant risk factor for the development of SSI, 21,24 was not related to any increase in infection rate in our study.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Previous epidemiologic studies of wound infection rate also found that older animals (>8years) were more likely to develop SSI. 23 Duration of anesthesia, previously found to be a significant risk factor for the development of SSI, 21,24 was not related to any increase in infection rate in our study.…”
Section: Discussionmentioning
confidence: 40%
“…8,[21][22][23][24][25][26][27] We were looking specifically at SSI in cases in which orthopedic implants had been placed, and over a longer period of time than most previous studies. Previously used definitions were therefore adapted to account for this.…”
Section: Definition Of Ssimentioning
confidence: 99%
“…Bacterial growth in propofol has been responsible for the outbreak of infections in humans and dogs 6,12 . Various methods have been sought to preserve propofol, including the addition of calcium EDTA and metabisulphite 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The Centres for Disease Control in the United States have indicated that propofol has played a role in small outbreaks of sepsis in human patients 6 . An increase in wound infections in veterinary medicine has been associated with the use of propofol 12 . Reuse of a propofol vial led to the death of a cat from septicaemia 2 hours after administration.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory depression and apnoea are reported as the most likely adverse events in dogs and to occur at a high incidence [40,41]. Propofol administration is associated with a higher rate of surgical wound infections than other anaesthetics [42,43].…”
Section: Gaba(a) Receptorsmentioning
confidence: 99%